2015
DOI: 10.1080/10803548.2015.1028224
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory chest movement measurement as a chair quality indicator – preliminary observations

Abstract: Regardless of the constantly increasing time man is spending in a sitting position, there is still a lack of objective chair quality assessment criteria. The aim of this paper is to find the answer to whether respiratory chest movement measurements can be a chair quality indicator. The study included 34 participants (mean 34.7 years ± 5.2). Their chest movements were assessed using respiratory inductive plethysmography while sitting on two subsequent chairs. Significant differences in chest movements depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Figure 1, visualization of Musculoskeletal Disorders (MSDs) Cobblers complaints with the highest pain complaint rate of 50%. The findings of Hutabarat [6], Andriani et al [7], Szczygieł et al [8], and Zein et al [9] proved that work activity in sitting conditions has a high level of musculosceletal disorders due to muscle tension. It is mentioned that the need for interlude activities such as rest by standing to straighten the condition of the back [10].…”
Section: Figure 1 Complaint Rate Of Musculoskeletal Disorders (Msds) ...mentioning
confidence: 97%
“…Figure 1, visualization of Musculoskeletal Disorders (MSDs) Cobblers complaints with the highest pain complaint rate of 50%. The findings of Hutabarat [6], Andriani et al [7], Szczygieł et al [8], and Zein et al [9] proved that work activity in sitting conditions has a high level of musculosceletal disorders due to muscle tension. It is mentioned that the need for interlude activities such as rest by standing to straighten the condition of the back [10].…”
Section: Figure 1 Complaint Rate Of Musculoskeletal Disorders (Msds) ...mentioning
confidence: 97%
“…Many reports have suggested that respiratory function is affected by changes in posture, such as standing or sitting [11][12][13]. However, there are few studies on wheelchairs and chairs [14,15]. Thus, this study aimed to clarify that use of an ABSW improves respiratory functioning.…”
Section: Introductionmentioning
confidence: 94%
“…Sitting in each chair took 5 minutes. This time was needed to acclimate to the chair, find a comfortable position, and regulate breathing [14]. After that, we assessed the subject's posture and measured the gas exchange.…”
Section: Measurement and Analysis Of Posture And Gas Exchangementioning
confidence: 99%
“…Há diferenças na mobilidade do tórax dependendo do tipo de cadeira. Essas diferenças consideraram as mudanças no percurso respiratório (superior e inferior) e o tamanho da amplitude do movimento respiratório (Ackermann et al, 2014;Szczygieł et al, 2015).…”
Section: Introductionunclassified